Influence of edaphic factors on the structure and distribution of plant species in and around Mekeiman Marsh Wetland, Northeast of Algeria - Moundji Touarfia; NOUREDDINE BOUALI; ABDELKADER DJOUAMAA; MOHAMED CHERIF MAAZI; MOUSSA HOUHAMDI (Society for Indonesian Biodiversity, 2021)
Abstract. Touarfia M, Bouali N, Djouamaa Ak, Maazi MC, Houhamdi M. 2021. Influence of edaphic factors on the structure and distribution of plant species in and around Mekeiman Marsh Wetland, Northeast of Algeria. Biodiversitas 22: 3219-3228. Understanding the environmental factors that influence plant species composition and distribution is essential for successful management of biodiversity. Hence, the purpose of the present study was to assess plant species composition and distribution in a freshwater wetland Mekeiman Marsh, Northeastern Algeria and to analyze the influence of environmental factors on local plant species. To explore the distribution of plant species in this Marsh and analyze their associations with edaphic soil factors, the mapping and types of plant species in this area were analyzed by MapInfo and principal component analysis (PCA) ordination. For this purpose, four stations were chosen according to a stratified sampling method and phytosociological surveys were carried out in 12 plots, which were sampled using the Braun- Blanquet method. Multivariate analyses were used to determine the relationship between plant species distribution and edaphic factors. The R i386 (version 4.0.3) software was used for data analysis. We have identified 48 plant species belonging to 21 families. Results of biological types in the study area revealed the dominance of hemicryptophytes and therophytes, which indicates the presence of therophytization in this Marsh. Spatial distribution maps showed that plant species were divided into two categories viz. sparse and scattered plants according to the humidity gradient. The most important edaphic factors associated with plant species in Mekeiman Marsh were Sodium, Phosphorus, active limestone, Magnesium, clay, organic matter, C/N and Azot. By combining mapping and influence of edaphic factors on the structure and distribution of plant species in this wetland, it was known that the plant assemblages of this Marsh make disproportionately important contributions to wetland-level diversity. By combining mapping and influence of edaphic factors on the structure and distribution of plant species in this wetland, the plant assemblages of this Marsh make disproportionately important contributions to wetland-level diversity.